From cents to half-cents and its liquidity impact. Issue 3 (10th November 2014) - Anderson, Hamish D.; Peng, Yuan
Abstract : Purpose: – The purpose of this paper is to examine the impact on stock liquidity following the reduction of minimum tick size from 0.01 to 0.005 for a selection of dual-listed and property stocks on the New Zealand Exchange (NZX) during 2011. Design/methodology/approach: – Various liquidity measures were examined six months either side of the change in minimum tick size for the eligible stocks and these were compared to a sample of stocks matched on similar liquidity characteristics. Liquidity measures examined in the paper include quoted and effective spread, volume, depth and binding-constraint probability. Findings: – After controlling for firms matched on similar pre-period liquidity characteristics both spread and depth decline significantly. Evidence that small firms experience significant declines in trading activity was also found, and while firms with higher binding-constraints probability have greater declines in spread, their decline in depth is greater still. Research limitations/implications: – The small sample of 17 stocks eligible for the 0.005 minimum tick size potentially impacts on the strength of the statistical analysis. As such, it is harder to detect statistically significant changes in liquidity. Practical implications: – These findings have important implications for policymakers as the hoped for benefits of smaller tick increments may only be fully realized by larger more active stocks. Originality/value: – The paper examines the impact of a change in minimum tick size on eligible New Zealand Exchange (NZX) stocks to determine whether it meet the stated NZX goal of boosting liquidity.